Preparedness for Protecting the Health of Community-Dwelling Vulnerable Elderly People in Eastern and Western Japan in the Event of Natural Disasters. Issue 2 (2nd April 2016) - Tsukasaki, Keiko; Kanzaki, Hatsumi; Kyota, Kaoru; Ichimori, Akie; Omote, Shizuko; Okamoto, Rie; Kido, Teruhiko; Sakakibara, Chiaki; Makimoto, Kiyoko; Nomura, Atsuko; Miyamoto, Yukari
ABSTRACT: We clarified the preparedness necessary to protect the health of community-dwelling vulnerable elderly people following natural disasters. We collected data from 304 community general support centres throughout Japan. We found the following in particular to be challenging: availability of disaster-preparedness manuals; disaster countermeasures and management systems; creation of lists of people requiring assistance following a disaster; evacuation support systems; development of plans for health management following disasters; provision of disaster-preparedness guidance and training; disaster-preparedness systems in the community; disaster information management; the preparedness of older people themselves in requiring support; and support from other community residents.